2016
DOI: 10.1007/s00109-016-1446-8
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adipocyte-derived extracellular vesicles are novel markers of metabolic stress

Abstract: We recently reported that stressed adipocytes release extracellular vesicles (EVs) that act as “find me” signals to promote macrophage migration and activation. In this study we performed a comprehensive characterization of stressed adipocyte-derived EVs, assessing their antigenic composition, lipidomics, and RNA profiles. Perilipin A was identified as one of the adipose-specific proteins and studied as a potential novel biomarker to detect adipocyte-derived EVs in circulation. Circulating EVs were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
115
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(145 citation statements)
references
References 47 publications
11
115
1
2
Order By: Relevance
“…miR-93-5p and miR-203-3p) had been reported to negatively regulate osteogenesis (Table S3) (Kennell et al, 2008;Hamam et al, 2014;Yang et al, 2012;. Eguchi et al also analyzed the miRNAs in adipocytes derived from EVs and detected several adipogenic miRNAs (including miR-148a-3p, miR-181a-5p, miR30a-5p, miR-125b-5p) (Eguchi et al, 2016), which is consistent with our results (Table S3).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…miR-93-5p and miR-203-3p) had been reported to negatively regulate osteogenesis (Table S3) (Kennell et al, 2008;Hamam et al, 2014;Yang et al, 2012;. Eguchi et al also analyzed the miRNAs in adipocytes derived from EVs and detected several adipogenic miRNAs (including miR-148a-3p, miR-181a-5p, miR30a-5p, miR-125b-5p) (Eguchi et al, 2016), which is consistent with our results (Table S3).…”
Section: Discussionsupporting
confidence: 91%
“…Inhibition of miR-450a-5p does not arrest Exo-AT-mediated adipogenesis completely. Eguchi et al performed a comprehensive protein content characterization of EVs derived from stressed adipocytes using tandem mass spectroscopy (LC-MS/MS) and found that the functions of proteins in EVs were mainly involved in translation, carbohydrate and lipid metabolism, cytoskeleton, extracellular matrix, ribonucleoproteins and nucleosomes (Eguchi et al, 2016). Connolly et al have reported that EVs from adipocytes are enriched in markers of adipogenesis (such as PREF-1, also known as DLK1, and PPARγ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports found that obesity leads to an increase in EV release in rodent animal models . However, we did not detect any differences in the concentration of circulating EVs found in subjects with obesity (not shown).…”
Section: Discussioncontrasting
confidence: 87%
“…[24] Previous reports found that obesity leads to an increase in EV release in rodent animal models. [15,25] However, we did not detect any differences in the concentration of circulating EVs found in subjects with obesity (not shown). However, in agreement with [26] the model of hypoxic 3T3-L1 adipocytes produced more EVs compared to normoxic cells, a phenomena seen in other hypoxic cell types.…”
Section: Discussionmentioning
confidence: 61%
“…It is noteworthy that increased levels of different EVs subpopulations are well associated with metabolic syndrome and obesity . Recent studies demonstrate that obese patients show higher levels of plasma EVs compared with normal weight healthy individuals . Furthermore, chronic inflammation, metabolic stress, and prothrombotic state of obese individuals may be factors triggering the release of EVs or EVs‐related proteins released from circulating cells .…”
Section: Introductionmentioning
confidence: 99%